ESS 이동형 시험장비용 운영시스템의 개발과 모의검증 - 신제석(Je-Seok Shin); 한현규(Hyun-Gyu Han); 김진태(Jin-Tae Kim); 이승민(Seung-Min Lee); 박찬욱(Chan-Wook Park); 임건표(Geon-Pyo Lim) (전기학회 논문지 P권, 67(3), 2018)
The performance test for 376MW ESS for frequency regulation currently operating in 13 substations is conducted based on the test procedure in the first and second steps. In the first step, components of ESS is moved to the certification authority where the test equipment is located in order to be proceeded with the test. In the second step, the performance test is conducted manually for the ESS equipments installed on site using the movable measurement equipment, and thus it can only be performed on some limited test items and requires a lot of time and manpower. Therefore, mobile test equipment for ESS(MOTES) is being developed that can perform automatically more test items for ESS in the field using the MOTES, and reduce manpower and time. To do this, an algorithm and a prototype of the operating system(MOS) are also being developed that can control MOTES automatically. In this paper, a development of the MOS prototype is introduced and then a simulation is performed to verify the prototype and its algorithm before the field demonstration.